2000
DOI: 10.1002/j.2050-0416.2000.tb00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Whisky Flavour Reference Compounds by Scottish Distillers†

Abstract: A set of 16 compounds was selected from the literature as potential flavour standards for whisky profiling: acetic acid (sour), diacetyl (buttery), dimethyl tri sulphide (sulphury), ethyl hexanoate (fruity-appley), ethyl laurate (soapy), furfural (grainy), geraniol (floral), guaiacol (smoky), hexanal (grassy), iso-amyl acetate (fruity-banana), iso-valeric acid (sweaty), maltol (sweet), phenyl ethanol (floral), vanillin (vanilla), 4-vinyl guaiacol (spicy) and whisky lactone (coconut).Each compound, at 90% recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Although, this may be thought as counterintuitive in that people enjoyed the food more but ate less, the authors suggested that soft music and lights may actually slow consumption, thus making people eat less rapidly and hence enjoy their food more. Indeed, this is consistent with the idea that eating more slowly is related to higher satisfaction levels and lower energy intake [24].…”
Section: On the Multisensory Manipulation Of The Atmospheresupporting
confidence: 89%
“…Although, this may be thought as counterintuitive in that people enjoyed the food more but ate less, the authors suggested that soft music and lights may actually slow consumption, thus making people eat less rapidly and hence enjoy their food more. Indeed, this is consistent with the idea that eating more slowly is related to higher satisfaction levels and lower energy intake [24].…”
Section: On the Multisensory Manipulation Of The Atmospheresupporting
confidence: 89%
“…3 Lee et al recently suggested that n-hexanal by itself could not explain the 'grassy' flavour in malt whisky. 4 Thus, the compounds that give malt whisky a green note have *Correspondence to: K. Hosoi, Institute for Production Research and Development, The Nikka Whisky Distilling Co. Ltd. 967 Matsuyama Masuo, Kashiwa, Chiba 277-0033, Japan. been sufficiently identified.…”
Section: Introductionmentioning
confidence: 99%
“…In beverage industry the oils are used for soft drink of cola-type, beer, whisky and wine [4][5][6]. The adding aroma of nutmeg essential oils on these products linked to ICSAFS Conference Proceedings spicy aroma.…”
Section: Introductionmentioning
confidence: 99%